Perkembangaan Biji dan Komponen Hasil Tiga Verietas Kedelai (Glicyne max (L) Merrill) dengan Pemberian Giberelin - Christian, Junjungan Rio; Rasyad, Aslim; Nurhidayah, Tengku (Jurnal Agro Teknologi Tropika, 2016)
Plant growth regulator play an important role in contributing internal mechanisms of plant growth by interacting with some metabolic process, so that it could be required in enhancing crop production. The objective of this research was to observe the effect of giberelin on seed development, yield potential and seed quality of three soybean varieties. Afield experiment was conducted and arranged in split plot design with giberelin concentration as main plot and soybean varieties as subplot. Gibberellin concentration used consisted of 0 ppm, 125 ppm and 250 ppm. Three Soybean varieties were Grobogan, Wilis and Kaban. Parameter Observe were seed water concentration, seed dry weight, seed growth rate, effective filling period, number of poods per plant, grain weight per plant, grain yield m-2, 100-seed weight, seed protein and oil content. The result of this research indicated that application of Gibberellin did not significantly affect soybean seed development but increased soybean seed yield potential and slightly improved the quality of soybean seeds in 3 varieties tested.